PERAN ORANG TUA DALAM PEMBELAJARAN DARING TERHADAP KEMAMPUAN KOGNITIF ANAK DI SDN 1.2 PANGELAK - Dea A’iwara Selena; Paulina Maria E.W; Silvester Adinuhgra (Sepakat : Jurnal Pastoral Kateketik, 2021)
This study aims to determine the role of parents in online learning on children's cognitive abilities, inhibiting and supporting factors experienced by parents at SDN 1.2 Pangelak. Through this study, it is hoped that parents can realize how important parental involvement in online learning towards children's cognitive abilities in Catholic Religious Education subjects during the covid-19 pandemic. The type of research used in this research is descriptive qualitative research. This research was conducted on May at SDN 1.2 Pangelak. The informants are 14 people consisting of the Principal, 1 Catholic Religion Teacher, 6 parents and 6 students. Data collection techniques through interviews and documentation. The data analysis technique used is the model of Miles and Huberman which consists of three stages, data reduction, data presentation and conclusion drawing.